COVID-19 Pandemic: The Causative Agent is New, The Problem is Old - Klepikov, Igor (International Journal of Coronaviruses, 2021)
A perspective situates SARS-CoV-2 within longstanding public health challenges, emphasizing preparedness, surveillance, and the recurrent lessons of outbreak management with examples for practice.
Keywords: pneumonia; COVID-19; pathogenesis; SARS-CoV-2